Clusterin as a potential marker of brain ischemia-reperfusion injury in patients undergoing carotid endarterectomy. (3rd July 2019) - Iłżecka, Joanna; Iłżecki, Marek; Grabarska, Aneta; Dave, Shawn; Feldo, Marcin; Zubilewicz, Tomasz
Abstract: Introduction: Carotid endarterectomy (CEA) is a surgical procedure used in the prevention of ischemic stroke. However, this procedure can cause complications of ischemia-reperfusion injury to the brain. Clusterin (CLU) is a cytoprotective chaperone protein that is released from neurons in response to various neurological injuries. The objective of the study was to report the changes in serum CLU concentrations of patients undergoing CEA. Materials and methods: The study involved 25 patients with severe internal carotid artery stenosis. Serum samples were taken from patients at three different times: within 24 hours preoperatively to CEA, 12 hours postoperatively, and 48 hours postoperatively. Serum CLU concentrations were measured using a commercially available enzyme-linked immunosorbent assay. Results: When compared to concentrations preoperatively, the serum CLU concentration initially decreased during the 12 hours following CEA. However, 48 hours following the procedure there was an increase in the CLU concentration. After statistical analysis, differences were detected in serum CLU concentration between all three recorded measurements ( P  < 0.05). Conclusion: Data from our study indicate that serum CLU concentrations are affected after CEA. We hypothesize that serum CLU concentrations may depend on brain ischemia-reperfusion injury following this surgical procedure.